A pediatric patient with chronic enteropathy associated with SLCO2A1 who underwent multimodal treatment including several surgeries: a case report - Jung, Yoojin; Chung, Jaehee; Yoo, Inhyuk (Frontiers in Surgery, 2025)
IntroductionChronic enteropathy associated with SLCO2A1 gene (CEAS) is a rare protein-losing enteropathy primarily recognized in Asia. Its uncommon nature and limited research usually complicate diagnosis and treatment. This review examines the course of a pediatric patient with CEAS, who underwent three surgeries during medical treatment.Case presentationA 12-year-old girl was referred for significant anemia and hypoalbuminemia during evaluation for short stature. Initial lab results included hemoglobin of 6.1 g/dl, normal CRP, and positive stool tests, without hematochezia. Capsule endoscopy revealed chronic ulcers and strictures in small bowel, and genetic testing identified a variant in SLCO2A1 gene, finally confirming CEAS. Because the capsule kept retained for 19 days, surgical removal was performed. Alongside the incision made at ileum, extensive circular stenoses were observed. Postoperatively, the patient was started on steroid and Azathioprine. After three months, she visited the emergency room with abdominal pain and fever. CT revealed diffuse free air and abscess, but no definite perforation was identified during emergency surgery, suggesting it was sealed-off. Two weeks after discharge, infliximab treatment was initiated. But she returned with vomiting a few days after second infusion. CT showed small bowel ischemia due to closed-loop obstruction, prompting urgent surgery. Multiple fibrotic bands were twisting part of jejunum, but the strictures seemed nearly normalized compared to earlier findings. We concluded that her disease was not worsening, and the last surgery was rather due to postoperative adhesions.DiscussionThis case highlights the challenges in early diagnosis of CEAS, given its rarity and nonspecific symptoms. However, it should be included in differential diagnosis for atypical clinical findings, with genetic testing as a potential diagnostic tool. Also, long-term immunosuppressive therapy often leads to complications requiring multiple surgeries, so minimally invasive approaches should always be considered. Additionally, the resolution of circular stenosis seen in the final surgery during infliximab treatment indicates a reversible component. Further research for effective treatment for CEAS is essential.